Transitional care experiences of caregivers of preterm infants hospitalized in a neonatal intensive care unit: A qualitative descriptive study - Ruo Han Ma; Qing Zhang; Zhi Hong Ni; Hai Tao Lv (Wiley, 2021)
Abstract Aim To describe the transitional care experiences and nursing needs of caregivers of preterm infants hospitalized in neonatal intensive care units (NICUs). Design A qualitative descriptive study. Methods We conducted semi‐structured interviews with the 24 caregivers of preterm infants admitted to Children's Hospital, Soochow University. All data were collected by a trained and experienced interviewer. The caregivers' experiences were described using qualitative content analysis. Results Six Five themes emerged from the analysis: (a) uncertainty about the disease; (b) anxiety due to restricted visitation; (c) exhaustion from overwork; (d) emotional depression; (e) low care ability; (f) a variety of channels for help and a positive response. This study provides a basis for understanding the needs of their caregivers so that effective coping strategies can be implemented. Nurses' education and practice should focus on understanding the real experiences of the parents of preterm infants during transitional nursing.